Resveratrol metabolites inhibit human metastatic colon cancer cells progression and synergize with chemotherapeutic drugs to induce cell death. Issue 7 (14th March 2013) - Aires, Virginie; Limagne, Emeric; Cotte, Alexia K.; Latruffe, Norbert; Ghiringhelli, François; Delmas, Dominique
<x xml:space="preserve">Abstract</x> Scope Resveratrol (RSV) has been proposed to prevent tumor growth; nevertheless, these preventive effects are controversial since RSV pharmacokinetics studies show a low bioavailability. Recent clinical trials show that patients with colorectal cancer and receiving oral RSV have high levels of RSV conjugates in the colorectum, mainly RSV‐3‐O‐sulfate (R3S), RSV‐3‐O‐glucuronide, and RSV‐4′‐O‐glucuronide. However, their potential biological activity has not yet been established. This study thus investigated in human colorectal cancer cell lines whether RSV main metabolites retain anticarcinogenic properties as their parental molecule. Methods and results Proliferation, apoptosis assays and cell cycle analysis were performed to study the effect of RSV, R3S, RSV‐3‐O‐glucuronide, or RSV‐4′‐O‐glucuronide alone or of a mixture of the three metabolites. R3S inhibits colon cancer cells proliferation and an accumulation of cells in S phase. Interestingly, the mixture induced a synergistic effect. This process was associated with an induction of DNA damages and apoptotic process, which allowed sensitization of colon cancer cells to the anticancer drugs. Conclusion Altogether, our data provide significant new insight into the molecular mechanism of RSV and support the notion that despite low bioavailability in vivo, RSV biological effects could be mediated by its metabolites.